A survey of antibodies to pestivirus in sheep in the Republic of Ireland - O'Neill Ronan G; O'Connor Michael; O'Reilly Patrick J (Irish Veterinary Journal, 2004)
Sera from 1,448 adult ewes in 91 flocks, representing all 26 counties in the Republic of Ireland, were examined for pestivirus antibodies using a commercially available ELISA which detected IgG1 antibody to border disease virus. Eighty-one sheep (5.6%) in 42 flocks (46.0%) were antibody-positive. Within infected flocks, the mean seroprevalence level was 11.4% with a range of 6.3% to 30.0%. The highest antibody prevalence was detected in sheep from central lowland counties of Ireland. Comparative neutralisation testing of 42 ELISA-positive sera detected geometric mean antibody titres of 136 to the NADL strain of bovine viral diarrhoea virus (BVDV), 92 to the Moredun strain of border disease virus and 21 to the 137/4 strain of border disease virus. These results suggest that BVDV may be the major ruminant pestivirus infecting sheep in Ireland. Although there are high numbers of infected flocks, many sheep within such flocks remain antibody-negative and are at risk of giving birth to lambs with congenital border disease.